Transparency in public procurement: The case of Slovenia - Matej Kirn; Lan Umek; Iztok Rakar (DANUBE: Law, Economics and Social Issues Review, 2019)
Public procurement is one of the key points of contact between public administration and the economy, while the amount of public resources is a possible source of conflict of interest and corruption. The article aims to contribute to improvements in public procurement legislation and practice. The article examines the practice of supervisory bodies and assesses the frequency of violations of the principle of transparency. The main findings of the article are that over the years of application of the Public Procurement Act in versions ZJN-2 and ZJN-3, the number of violations of the basic principle of transparency increased - the most frequent violations concerning discriminatory criteria set by the contracting authorities and their implementation in the selection phase - and that local municipal bodies violated the principle of transparency more often than state bodies.
Keywords: 330; Public Procurement; Supervision; Central Government; Municipalities; Principle of Transparency